2022
DOI: 10.1111/jwas.12920
|View full text |Cite
|
Sign up to set email alerts
|

Water quality, waste production, and off‐flavor characterization in a depuration system stocked with market‐size Atlantic salmon Salmo salar

Abstract: Land-based Atlantic salmon, Salmo salar, grow-out facilities utilize depuration to remediate off-flavor. Water used in this process is either discharged or repurposed as supply water in recirculating aquaculture systems (RAS). Both approaches require an understanding of water quality and waste production for water treatment decisions and compliance with pollution discharge standards; however, these data were lacking. Therefore, a study was carried out to characterize these parameters. To begin, 311 salmon(5-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The characterization of the synthetic wastewater was carried out, the pH and conductivity analysis with the multiparameter HACH HQ40d, for which the sample of 100 mL of synthetic water was placed in a beaker and the reading was done with the equipment. Color analysis, COD, hexavalent chromium (Cr +6 ) and copper (Cu) were performed using the HACH DR500 spectrophotometer following the different processes stipulated in the water analysis manual (Davidson et al, 2022;Hach Company, 2000):…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of the synthetic wastewater was carried out, the pH and conductivity analysis with the multiparameter HACH HQ40d, for which the sample of 100 mL of synthetic water was placed in a beaker and the reading was done with the equipment. Color analysis, COD, hexavalent chromium (Cr +6 ) and copper (Cu) were performed using the HACH DR500 spectrophotometer following the different processes stipulated in the water analysis manual (Davidson et al, 2022;Hach Company, 2000):…”
Section: Methodsmentioning
confidence: 99%
“…52 Most recently, RAS reared Atlantic salmon of 5-6 kg were fasted for 1 day and then transferred to depuration tanks where they were fasted for another 7 days. 190 Here, geosmin and 2-methylisoboreal levels in water and fish were generally low, and it was concluded that a 7-day depuration period was excessive and that the fish could have been harvested after just 2-3 days, as long as gut evacuation was complete. 189 These examples suggest it is possible to manage and mitigate off-flavour compounds in RAS by manipulating environmental, microbial, and technological conditions.…”
Section: Feed Withdrawal In Rasmentioning
confidence: 99%
“…The plastic cans with water were securely corked and stored in ice-packed containers before transporting them to the laboratory for analysis [40]. This was done within six hours of collection as advised by Davidson, et al [41].…”
Section: Sample Collectionmentioning
confidence: 99%